Chromosome-level genome of the globe skimmer dragonfly (Pantala flavescens). (4th April 2022) - Liu, Hangwei; Jiang, Fan; Wang, Sen; Wang, Hengchao; Wang, Anqi; Zhao, Hanbo; Xu, Dong; Yang, Boyuan; Fan, Wei
ABSTRACT: Background: The globe skimmer dragonfly ( Pantala flavescens ) is a notable Odonata insect distributed in nature fields and farmlands worldwide, and it is commonly recognized as a natural enemy because it preys on agricultural pests and health pests. As one of the sister groups of winged insects, odonatan species are key to understanding the evolution of insect wings. Findings: We present a high-quality reference genome of P. flavescens, which is the first chromosome-level genome in the Palaeoptera (Odonata and Ephemeroptera). The assembled genome size was 662 Mb, with a contig N50 of 16.2 Mb. Via Hi-C scaffolding, 648 Mb (97.9%) of contig sequences were clustered, ordered, and assembled into 12 large scaffolds, each corresponding to a natural chromosome. The X chromosome was identified by sequence coverage depth. The repetitive sequences and gene density of the X chromosome are similar to those of autosomal sequences, but the X chromosome shows a much lower degree of heterozygosity. Our analysis shows that the effective population size experienced 3 declining events, which may have been caused by climate change and environmental pollution. Conclusions: The genome of P. flavescens provides more information on the biology and evolution of insects and will help for the use of this species in pest control.